Politik Agraria Kolonial dan Perlawanan Sosial di Jawa Timur: Legenda Sarip Tambak Oso - Muhdi, Muhdi; Rachmawati, Eva Nur (Jurnal Sejarah Citra Lekha, 2025)
This article examines colonial agrarian politics in Eastern Java following the enactment of the Agrarische Wet of 1870, focusing on the effects of land taxation policies on rural social inequality and on the interpretation of Sarip Tambak Oso’s actions as a form of popular social resistance to the colonial agrarian order. Employing the historical method within a historical, sociological approach, through heuristic, verification, interpretation, and historiographical stages, the analysis is grounded in Ralph Linton’s role theory and James C. Scott’s theory of everyday resistance. The study advances three principal findings. First, post-1870 colonial agrarian policy in Java did not constitute a liberating form of agrarian liberalism; rather, it established a hierarchical and exploitative land-tenure regime through the doctrine of domein verklaring. Second, colonial land taxation functioned as a mechanism of power that reproduced rural social stratification, intensified economic inequality, and accelerated the proletarianization of smallholders. Third, within this structurally unequal agrarian context, Sarip Tambak Oso, popularly remembered as a “thief for the people”, can be understood as embodying a form of moral-economic social resistance that challenged colonial hegemony through symbolic and redistributive action. Sarip represents subaltern agency, underscoring that colonial conflict in Java was fundamentally rooted in struggles over land, taxation, and rural social justice. Theoretically, this article argues that colonial agrarian policy produced structural domination, while Sarip Tambak Oso’s resistance expands the analytical scope of everyday resistance and role theory as forms of subaltern political praxis.